Genetic diversity of Thymus sibthorpii Bentham in mountainous natural grasslands of Northern Greece as related to local factors and plant community structure - Eleni M. Abraham (2018)
© 2017 Elsevier B.V. The local scale genetic diversity of Thymus sibthorbii, an aromatic species of the Greek flora, was studied both in relation to its habitat characteristics. The study was conducted in Cholomontas mountain, northern Greece at altitudes of 760–870 m. Genetic material from Southern and Northwestern exposures and from different grazing intensities within each exposure, was studied using ISSR molecular markers. The plant cover at each study site was measured and the floristic composition of the site was calculated. The grazing intensity affected the species composition and reduced the abundance of T. sibthorpii. The floristic diversity in terms of species richness, evenness and Shannon index (IF) was higher at the southern sites. Within population gene diversity (HE) ranged from 0.203 to 0.245 and Shannon index (IG) from 0.311 to 0.377. Most of the genetic diversity resided within populations (88%). Significant genetic differentiation was detected among the populations from the southern and northwestern sites, as well as among populations of each exposure. Genetic diversity of T. sibthorpii was not correlated to species diversity (richness and evenness), either within or between populations. Instead, genetic diversity was found to be positively correlated with environmental factors, such as N soil content and soil moisture.